Characterization of Environmental Conditions Conducive For Spread of Whitefly Population and Epidemic Development of Chilcv (Global Journal of Science Frontier Research, 2018)
Chilli (C.annum L.) is one of the main solaneaous crop in Pakistan and treated by many viral diseases. This experiment was performed to check the effect of environmental conditions on whitefly population and disease incidence development as well as correlation and regression analysis of environmental factors like maximum, minimum temperature, relative humidity, rainfall and wind speed with whitefly population on Chilli plants. For the determination of effect of environmental factors on the incidence of virus and whitefly Population, five environmental factors were kept in consideration which were maximum temperature, minimum temperature, relative humidity, rainfall and wind pace. The data recorded on disease incidence and whitefly population was subjected to correlation and regression analysis for determining the relationship between environmental variables and incidence of disease and whitefly population. All environmental parameters including (maximum temperature, minimum temperature, and relative humidity) showed positively significant correlation and wind speed and rainfall showed negatively significant correlation.
Keywords: chiLCV; regression; correlation; epidemiology; conducive